2006
DOI: 10.3386/w12770
|View full text |Cite
|
Sign up to set email alerts
|

Population Aging and Intergenerational Transfers: Introducing Age into National Accounts

Abstract: In all societies intergenerational transfers are large and have an important influence on inequality and growth. The development of each generation of youth depends on the resources that it receives from productive members of society for health, education, and sustenance. The well-being of the elderly depends on familial support and a variety of social programs. The National Transfer Accounts (NTA) system provides a comprehensive approach to measuring all reallocations of income across age and time at the aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 48 publications
0
64
0
11
Order By: Relevance
“…These data form part of the National Transfer Accounts (NTA) project (www.ntaccounts.org). National Transfer Accounts (NTA) is a system for measuring economic flows by age at the aggregate level in a manner consistent with National Accounts [MASON et al, 2009]. NTAs provide a complete and coherent measurement of economic relationships between population groups (by age, gender, socioeconomic status) within a national economy in the same way that National Accounts measure economic relationships between sectors (household, production, government).…”
Section: S11mentioning
confidence: 99%
“…These data form part of the National Transfer Accounts (NTA) project (www.ntaccounts.org). National Transfer Accounts (NTA) is a system for measuring economic flows by age at the aggregate level in a manner consistent with National Accounts [MASON et al, 2009]. NTAs provide a complete and coherent measurement of economic relationships between population groups (by age, gender, socioeconomic status) within a national economy in the same way that National Accounts measure economic relationships between sectors (household, production, government).…”
Section: S11mentioning
confidence: 99%
“…The difference between consumption and labour income in NTA offers a measure for the average economic dependency (if positive) or the economic ability to support others (if negative) at each age and is termed life cycle deficit (LCD) (Mason et al, 2006). It can also be derived by an rearrangement of the terms in Equation (1) C − YL…”
Section: An Economic Dependency Ratio: the Life Cycle Deficitmentioning
confidence: 99%
“…The population projections are paired with NTAs for the seven countries for which they are available from the National Transfer Accounts Project (Table 1). 4 The concept of NTAs is described concisely and in-depth elsewhere (Mason et al 2006;Prskawetz and Sambt 2014;UN 2013). Below we outline only the components that are essential to our application, together with a few caveats.…”
Section: National Transfer Accounts and Population Datamentioning
confidence: 99%
“…They observed that the National Transfer Accounts (NTAs) (Mason et al 2006) show that for many countries, pension transfers make up the largest share of public old-age transfers until rather late in life. Until recently, the pension ages in many countries had been unchanged for decades, with a downward trend in the average age of retirement (OECD 2013).…”
Section: Introductionmentioning
confidence: 99%